2019
DOI: 10.3389/fpsyg.2019.01279
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Alternative Strategies to Cope With the Subtropical Climate of Tokyo 2020: Impacts on Psychological Factors of Performance

Abstract: The thermal discomfort caused by a hot or hot-wet climate can have negative effects on human performance. The 2020 Summer Olympic and Paralympic Games will take place in Tokyo’s hot and humid summer period, possibly exposing athletes to severe environmental stressors. In addition to technical, tactical, physical and nutritional preparation, Olympians and Paralympians need an optimal psychological state to turn in their best performances, especially in terms of emotional control, concentration and motivation. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
0
23
0
6
Order By: Relevance
“…Hwang and Cheng (2007) observed that the Taiwanese (living in a hot and humid climate) have a high tolerance of humidity because they are acclimatized to it. It can be assumed that the participants of the current study were more tolerant of TC and experienced less NA probably due to acclimatization (Coudevylle et al, 2019). Fatigue can also influence task performance (Lan et al, 2011).…”
Section: Environmental Perceptionmentioning
confidence: 84%
See 2 more Smart Citations
“…Hwang and Cheng (2007) observed that the Taiwanese (living in a hot and humid climate) have a high tolerance of humidity because they are acclimatized to it. It can be assumed that the participants of the current study were more tolerant of TC and experienced less NA probably due to acclimatization (Coudevylle et al, 2019). Fatigue can also influence task performance (Lan et al, 2011).…”
Section: Environmental Perceptionmentioning
confidence: 84%
“…We therefore recommend ''maîtres d'armes'' (i.e., fencing coaches) to favor training in AC in order to preserve positive affective states and aiming accuracy, except when competitions in TC are upcoming. Indeed, in a mini-review recently published, Coudevylle et al (2019) evoked strategies to cope with the TC of Tokyo Olympic/Paralympic Games 2020. The researchers suggested the use of subjective strategy as cold suggestion and the use of objective intervention as cooling vest, provided that it does not disturb the athletes, during timeouts in duel sports in tropical environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, first and foremost, this type of investigation can only be carried out on the basis of a thorough medical examination. Implementing psychological strategies to motivate athletes to keep up an effort can be extremely dangerous to their health, just as the administration of too much menthol can be ( Bain et al, 2015 ; Coudevylle et al, 2019 ). The priority of coaches should be to first take into account the athlete’s health and then optimize performance by improving thermal comfort through mental and objective techniques (e.g., pre-, per-, and post-cooling).…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, the brain plays the role of an effort regulator, anticipating and adapting instantaneously and continuously to ensure the effort required before the rupture of the physiological balance in the body. Thus, psychological parameters may come into play in the performance declines (see Coudevylle et al, 2019 ). The studies thus far that have focused on psychological parameters have mainly been oriented towards cognitive processes (e.g., reaction time, memory, and attention), perceptions (e.g., RPE, thermal comfort), or affect (see Robin et al, in press ).…”
Section: Introductionmentioning
confidence: 99%